PENGGUNAAN SUMUR RESAPAN UNTUK MENGURANGI GENANGAN AIR HUJAN DI KAMPUS KARANGMALANG UNIVERSITAS NEGERI YOGYAKARTA - Lutjito, Sudiyono AD, Didik Purwantoro (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2015)
ABSTRACTThe objectives of this studywas to solve the problem of floodwater due to the rainwater runoffand to reduce the flow rate of the runoff at the Colombo Street in front of the Faculty of SportScience, Yogyakarta State University (YSU). This study was conducted based on the existingprimary and secondary data. The data analysis to get the rainfall intensity was conducted usingthe analytical method that obtain the values of the standard deviation, the mean, the coefficientof variation, the asymmetry and kurtosis. From these values, it was obtained the types ofeligible distribution after going through the test to get the maximum rainfall in the period of 2years, 5 years, 10 years, 20 years and 25 years. Based on the data, the arch intensity wasexamined. The analysis showed if20% of YSU area is occupied by infiltration wells or if thereare 250 infiltration wells in which 1 infiltration well is used for the area of 350 m2, the need ofinfiltration wells will be covered and it is going to reduce the flow rate of the runoff in 0.552 m3/s.This is consistent with the concept of sustainable rainwater drainage system based on theconservation of ground Water. Essentially,it is a drainage system in which the rainwater fallingon the roof/pavement, is accommodated in a system of water absorption among othersinfiltration Wells therefore it will reduce the the floodwater runoff at the Colombo street. Anotherbenefit isthe infiltration wells will also increase the ground water level.Keywords: Rate of Flow, Infiltration Well, Rain Water